2017
DOI: 10.1097/dss.0000000000001084
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of Reversible Hyaluronic Acid Filler Injection Treated With Hyaluronidase

Abstract: Lower concentrations of hyaluronidase may be just as effective as higher concentrations to degrade HA filler in situations where the reversal of cutaneous augmentation with HA filler arises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 5 publications
3
41
0
3
Order By: Relevance
“…Recently, Wang et al (2017) used the same rabbit ear model to show that a subcutaneous injection of hyaluronidase is more effective than an intra-arterial injection. Moreover, the authors showed that (Juhasz, Levin, & Marmur, 2017;Rao, Chi, & Woodward, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wang et al (2017) used the same rabbit ear model to show that a subcutaneous injection of hyaluronidase is more effective than an intra-arterial injection. Moreover, the authors showed that (Juhasz, Levin, & Marmur, 2017;Rao, Chi, & Woodward, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding another brand of HA filler, Allergan JUV (Juvéderm Ultra 3, HA 24.0 mg/ml, lidocaine; Pharm‐Allergan, Irvine, CA), the results of its interaction with hyaluronidase are more inconsistent. Whereas Sall et al and Jones et al reported a strong resistance to degradation against bovine or ovine hyaluronidase (Jones, Tezel, & Borrell, ; Sall & Ferard, ), Rao et al as well as Juhász et al demonstrated that ovine or recombinant human hyaluronidase effectively degrades JUV (Juhasz, Levin, & Marmur, ; Rao, Chi, & Woodward, ).…”
Section: Discussionmentioning
confidence: 99%
“…Eigene unveröffentlichte Daten zeigen aber, dass Hyaluronidase in hautstrukturellen Zellen HA-Synthasen (HAS) signifikant und dosisabhängig induziert, ein transienter Verlust an HA somit also durch eine verstärkte HA-Neosynthese in Fibroblasten und Keratinozyten umgehend ausgeglichen wird. Ob sich aber tatsächlich auch alle Arten von HA-Fillern durch Hylase gleich effektiv oder überhaupt auflösen lassen, ist Gegenstand aktueller Forschung [31].…”
Section: Temporäre Fillerunclassified
“…In this case, 25 microkatals of bacterial recombinant hyaluronidase were injected per side, which is equivalent to 1500 UI of other types of hyaluronidase. 6,7 As the photographic sequence demonstrates, the enzymatic activity onset is immediate. The first photograph (Figure 1) was taken 60 seconds after the injection showing partial dilution and collapse of the nodule.…”
mentioning
confidence: 99%
“…The second photograph (Figure 2) shows the nodule with almost 50% of its content collapsed while the third photograph (Figure 3), taken 60 minutes after the injection, presents the affected area with a 90% reversal, demonstrating a great result thus compared with the 60 minutes results described by Juhász and collaborators by using animal-derived hyaluronidase. 6 Control photographic evidence was taken 7 days after the procedure showing the patient without any residue of the hyaluronic acid nodules (Figure 4).…”
mentioning
confidence: 99%